Optimización de la estructura de un compuesto de coordinación de cobre - Hernández Granda, Karol Yaritza (2018)
Abstract:The aim of the present study is to obtain the most probable molecular structure of the copper coordination compound [Cu(ttc)3]. Two new computational structural models optimized geometrically with the Gaussian 09 program are presented using the hybrid functional B3LYP and for the population analysis the AIMAll software was used. The molecular model [Cu(ttc)3]-tiona is proposed as the most stable structure compared to [Cu(ttc)3]-tiol and the original starting model. The elucidation proposal was reaffirmed by the properties obtained computationally carried out with the same level of theory and basis sets of the optimization. The calculated values of vibrational frequencies were compared with the experimental values of FTIR obtaining a correlation of 0.9958 for [Cu(ttc)3]-tiona. The molecular orbitals HOMO and LUMO, as well as the electrostatic potential agree that the nucleophilic sites are found in the S atoms of the ttc ligand, while the electrophilic ones belong to the Cu(I) ion. In addition, the possible interaction between the S-S bonds of the ligand is shown.